Effect of Stump Length on Postural Steadiness During Quiet Stance in Unilateral Trans-Tibial Amputee - P. Lenka; D.N.Tiberwala (Al Ameen Medical College, 2010)
Although force platform based Center of pressure (COP) measures of postural steadiness have been used to test the diagnostic significance of various cerebellar and labyrinthine lesions, but very few literature are available on amputees. The aim of this work is to measure the effect of stump length of Trance-Tibial amputee on postural steadiness during quiet stance. The COP variation, which is the major determinant of stability, has been evaluated. Twenty transtibial amputee patients (age: 34±9.57 years) participated in this study. Among them, ten patients were having stump length of (19.33±2.04 cm) and ten patients were having stump length of (9.2±0.91 cm). Postural stability is evaluated considering following factors like, AP range, ML range, RMS distance, mean distance, sway velocity, sway area and mean power frequency. The result shows that the mean value of all the measure parameters are having higher values in case of patients having shorter stump length than there counterpart. Therefore, it is concluded that transtibial amputee with longer stump length has better postural steadiness.